상향류식 혐기성 슬러지 블랭킷 반응조에 비교한 생물전기화학 반응조의 산성 주정폐수처리성능 - 풍경(Qing Feng); 송영채(Young-Chae Song); 유규선(Kyuseon Yoo); 반와리 랄(Banwari Lal); 난다쿠마르 쿱파난(Nanthakumar Kuppanan); 산죽타 수부디(Sanjukta Subudhi) (Daehan hwan'gyeong gonghag hoeji, 2016)
The performance of upflow anaerobic bioelectrochemical reactor (UABE), equipped with electrodes (anode and cathode) inside the upflow anaerobic reactor, was compared to that of upflow anaerobic sludge blanket (UASB) reactor for the treatment of acidic distillery wastewater. The UASB was stable in pH, alkalinity and VFAs until the organic loading rate (OLR) of 4.0 g COD/L.d, but it became unstable over 4.0 g COD/L.d. As a response to the abrupt doubling in OLR, the perturbation in the state variables for the UABE was smaller, compared to the UASB, and quickly recovered. The UABE stability was better than the UASB at higher OLR of 4.0-8.0 g COD/L.d, and the UABE showed better performance in specific methane production rate (2,076mL $CH_4/L.d$), methane content in biogas (66.8%), and COD removal efficiency (82.3%) at 8.0 g COD/L.d than the UASB. The maximum methane yield in UABE was about 407mL/g $COD_r$ at 4.0 g COD/L.d, which was considerably higher than about $282mL/g\;COD_r$ in UASB. The rate limiting step for the bioelectrochemical reaction in UABE was the oxidation of organic matter on the anode surface, and the electrode reactions were considerably affected by the pH at 8.0 g COD/L.d of high OLR. The maximum energy efficiency of UABE was 99.5%, at 4.0 g COD/L.d of OLR. The UABE can be an advanced high rate anaerobic process for the treatment of acidic distillery wastewater. 중화하지 않은 주정폐수를 처리할 때 상향류식 혐기성반응조에 전극을 배치한 생물전기화학반응조의 성능을 UASB 공정과 비교하였다. UASB 공정은 유기물부하율 4.0 g COD/L.d 이하에서 pH, VFA 및 알카리도 등에 있어서 안정한 상태를 유지하였지만, 4.0 g COD/L.d 이상의 유기물부하율에서는 불안정하였다. 그러나, 생물전기화학 반응조는 UASB 반응조에 비하여 유기물부하율 배가시 상태변수들의 변동폭이 작았으며, 빠르게 정상상태로 회복하였다. 생물전기화학 반응조는 4.0-8.0g COD/L.d의 높은 유기물부하율에서 상태변수들이 UASB 반응조에 비하여 안정하였으며, 유기물부하율 8.0 g COD/L.d에서 비메탄발생율(2,076mL $CH_4/L.d$), 바이오가스의 메탄함량(66.8%) 그리고 COD 제거율(82.3%) 등의 측면에서 UASB 반응조보다 우수하였다. 생물전기화학 반응조의 메탄수율은 유기물부하율 4.0 g COD/L.d에서 약 407mL/g $COD_r$로 최대값을 보였으며, 이 값은 UASB의 282mL/g $COD_r$보다 크게 높았다. 중화하지 않은 산성 주정폐수를 처리하는 생물전기화학 반응조의 전극반응에서 율속단계는 산화전극반응이었으며, 전극반응은 높은 유기물부하율에서 pH에 의해서 크게 영향을 받았다. 생물전기화학 반응조는 유기물부하율 4.0 g COD/L.d에서 99.5%의 최대에너지효율을 보였다. 중화하지 않은 산성 주정폐수를 처리하는 생물전기화학 반응조는 UASB 공정보다 진보된 고율 혐기성 기술이 될 수 있다.